Core-shell coated Raney nickel catalyst and preparation method thereof
Through the preparation method of core-shell coated Rainey nickel catalyst, the activity and stability of Rainey nickel catalyst is modified by using hydrothermal reaction and high-temperature sintering, which solves the problems of low activity and poor stability of traditional catalysts, and achieves efficient catalytic hydrogenation.
Patent Information
- Application Number
- CN202411872073.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing Rainey nickel catalysts have low activity and poor stability during use, and are prone to cause side reactions of impurities polymerization and condensation at high temperatures, resulting in coking of the catalyst bed and decreasing activity.
The core-shell coated Rainey nickel catalyst is prepared by hydrothermal reaction with glucose and Rainey nickel aqueous solution to form a carbon-coated Rainey nickel catalyst, and then calcined in an inert atmosphere and sintered at high temperature. The heteroatomic modification is performed using a phosphorus source to change the electron distribution of the nickel element.
The activity and stability of the catalyst are improved, making it suitable for efficient catalytic hydrogenation, solving the problems of low activity and poor stability of traditional catalysts, and reducing the preparation cost.
Smart Images

Figure CN119633847A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the fields of liquid-phase hydrogenation and industrial catalysis, and particularly relates to a core-shell coated Raney nickel catalyst, a preparation method of the core-shell coated Raney nickel catalyst, and an application thereof in the liquid-phase hydrogenation of ethylene glycol. Background Art
[0002] Ethylene glycol (EG) is an important chemical raw material, and its largest use is generally for the production of polyester resins (fibers and films), and the market demand in this regard is very large. When ethylene glycol is used as a raw material for producing polyester, it needs to reach extremely high purity, that is, polyester grade or national standard excellent grade. One of the indicators is the ultraviolet transmittance (UV value), which is used to represent the content of organic impurities that will affect the quality of polyester. Trace impurities generated during the production process cause the ethylene glycol product not to meet the 17 indicators specified in the national standard <<GB / T 4649-2018 Ethylene Glycol for Industrial Use>>. Polyester-grade ethylene glycol requires a purity greater than 99.9%, especially a relatively high requirement for the ultraviolet transmittance. The transmittance at 220 nm ≥ 75%, the transmittance at 275 nm ≥ 92%, and the transmittance at 350 nm ≥ 99%. The national standard ultraviolet transmittance index even exceeds the internationally common ASTM standard in the United States. In the ASTM E247007 polyester-grade ethylene glycol standard, the requirement for the transmittance of polyester-grade ethylene glycol at 220 nm is ≥ 70%, which is lower than the national standard requirement of ≥ 75%. In view of the strict national standard, it is very difficult for ethylene glycol enterprises to meet the requirements simply through rectification, and auxiliary means are needed for treatment to make the ultraviolet transmittance of the product meet the standard. The market urgently needs technologies for refining ethylene glycol to improve its product ultraviolet transmittance and increase the added value of the product. Therefore, it is of great significance to develop ethylene glycol refining catalysts and catalytic technologies that meet market demands and are suitable for industrial production.
[0003] As an important skeletal nickel catalyst, the discovery and application of Raney nickel catalyst (Raney-Ni) can be traced back to the 1830s and 1840s of the 19th century. This catalyst is widely used in organic reduction reactions due to its advantages such as low preparation cost, high selectivity, and high activity. Catalysis and dehalogenation reactions of aldehydes, olefins, nitriles, ketones, aromatic rings, nitro groups, etc. all rely on Raney nickel catalysts. In order to solve the problems of low activity and poor stability of traditional industrial Raney nickel catalysts during use. For Raney nickel-based catalysts with a high specific surface area, the most important thing is to modify them with heteroatoms to change the electron distribution of nickel elements to weaken their adsorption ability to hydrogen elements, and finally achieve efficient hydrogenation in industry. Summary of the Invention
[0004] The purpose of the present invention is to provide a preparation method of a core-shell coated Raney nickel catalyst to solve the deficiencies of complex catalyst preparation process, low catalyst activity, and poor stability in the existing methods.
[0005] The present invention also aims to provide a core-shell coated Raney nickel catalyst to solve the problem that the original catalyst activity is too high, and it is easy to cause impurity polymerization and condensation side reactions at high temperature, which will cause coking of the catalyst bed for a long time, resulting in a decrease in catalyst activity.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a core-shell coated Raney nickel catalyst comprises the following steps:
[0008] (1) adding glucose to the Raney nickel aqueous solution, stirring to make it uniformly mixed, and then placing it in a reactor for hydrothermal reaction to obtain a wet product;
[0009] (2) vacuum drying the wet product and then calcining it in an inert atmosphere to obtain a core-shell Raney nickel catalyst;
[0010] (3) The core-shell Raney nickel catalyst and a phosphorus source are sintered at high temperature under the protection of an inert gas to obtain a modified Raney nickel catalyst.
[0011] According to the method of the invention, glucose and a Raney nickel aqueous solution are subjected to hydrothermal reaction, and then sintered to prepare a carbon-coated Raney nickel catalyst, and then the carbon-coated Raney nickel catalyst is phosphated to prepare a modified Raney nickel catalyst.
[0012] In the present invention, the Raney nickel aqueous solution in step (1) is prepared by an alkali leaching method.
[0013] Furthermore, the specific process of preparing the Raney nickel aqueous solution by alkaline leaching is as follows: the nickel-aluminum alloy particles are mixed with the sodium hydroxide solution, slightly stirred and activated under heating conditions, and then allowed to stand for precipitation, and fresh sodium hydroxide is replaced overnight, washed with distilled water until neutral, and stored in distilled water for later use.
[0014] Furthermore, the nickel-aluminum alloy particles contain 48%-50% Ni by mass, and the rest is Al.
[0015] Furthermore, the heating temperature is 80-110° C., and the activation time is 4-8 hours.
[0016] In the present invention, the mass ratio of glucose to Raney nickel in step (1) is 1:2-1:4.
[0017] In the present invention, the temperature of the hydrothermal reaction in step (1) is 170-190° C., and the reaction time is 1-2 h.
[0018] In the present invention, the calcination temperature in step (2) is 780-820° C. and the calcination time is 5-6 hours.
[0019] Furthermore, in step (2), the inert atmosphere is argon.
[0020] In the present invention, the high temperature sintering temperature in step (3) is 250-550° C., and the heat preservation time is 2-3 hours.
[0021] In the present invention, the specific process of high-temperature sintering under the protection of inert gas in step (3) is as follows: in a dual-temperature zone tubular furnace, a quartz boat is loaded with a phosphorus source and placed in the upstream heating zone, and another quartz boat is loaded with a core-shell Raney nickel catalyst and placed at the upper end of the downstream heating zone; high-temperature sintering is performed under the protection of an argon atmosphere.
[0022] Furthermore, the phosphorus source is NaH2PO2.
[0023] Furthermore, the heating temperature of the upstream of the dual-temperature zone vacuum atmosphere tubular furnace is 300° C., and the heating temperature of the downstream is 350-550° C. The two temperature zones are heated simultaneously to reach the set temperature for heat preservation treatment.
[0024] In some embodiments of the present invention, the operation of introducing argon to exclude air is as follows: before the heating process, the gas is pumped three times and the time of introducing argon is 15 minutes; the argon flow rate of the gas path system during the heating process is set to 100s.ccm.
[0025] The specific parameters of the phosphorus source doping process in the vacuum atmosphere tube furnace in step (3) are: heating to 300° C. at a rate of 2° C. / min, and the flow rate of argon gas is 100 s.ccm.
[0026] A core-shell coated Raney nickel catalyst is obtained by the above preparation method.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The method for preparing a core-shell coated Raney nickel catalyst of the present invention first prepares a carbon-coated Raney nickel catalyst, then uses a phosphorus source to modify it through heteroatoms to change the electron distribution of the nickel element, and finally prepares a highly active and highly stable Raney nickel catalyst to make it suitable for efficient catalytic hydrogenation.
[0029] (2) The preparation method of the present invention is simple, low in cost, and the reaction conditions are easy to control, which provides a useful reference for the preparation of Raney nickel catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the XRD spectrum of the core-shell coated Raney nickel catalyst RaneyNi@CP core-shell catalyst obtained in Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0031] To facilitate the understanding of the present invention, the technical solution described in this invention will be described more comprehensively and meticulously in conjunction with preferred embodiments below. The present invention will be further described in conjunction with specific embodiments below so that those skilled in the art can better understand and implement the technical solution of the present invention.
[0032] Example 1
[0033] A method for preparing a core-shell coated Raney nickel catalyst comprises the following steps:
[0034] (1) adding glucose to the Raney nickel aqueous solution, stirring to make it uniformly mixed, and then placing it in a reactor for hydrothermal reaction to obtain a wet product;
[0035] The specific process is to prepare the Raney nickel aqueous solution by alkaline leaching. Raney nickel uses nickel-aluminum alloy particles with a mass fraction of 48%-50% Ni and the rest Al. It is mixed with a sodium hydroxide solution with a mass fraction of 20%. The temperature of the process does not exceed 50°C. After the bubbles are generated and weakened, the process is slightly stirred. After the bubbles are generated and weakened, they are slightly stirred and activated for 4 hours under the condition of heating at 80°C, and then allowed to stand and precipitate. Fresh sodium hydroxide is replaced overnight, washed with distilled water until neutral, and stored in distilled water for use. 5g of glucose is added to the aqueous solution containing 10g of Raney nickel, stirred for 2h, and a uniformly mixed solution is obtained.
[0036] (2) vacuum drying the wet product and then calcining it in an inert atmosphere to obtain a core-shell Raney nickel catalyst;
[0037] The specific process is as follows: the uniformly mixed solution in step (1) is allowed to stand, vacuum dried for four hours, and then placed in a tubular furnace and calcined at 800° C. for 5 hours in an argon atmosphere to obtain a core-shell Raney nickel catalyst Raney-Ni@C.
[0038] (3) The core-shell Raney nickel catalyst and a phosphorus source are sintered at high temperature under the protection of an inert gas to obtain a modified Raney nickel catalyst.
[0039] The specific process is as follows: During the synthesis process, in a dual-temperature zone tubular furnace, 1g NaH2PO2 is placed in a quartz boat located in the upstream central heating zone. 0.5g of core-shell Raney nickel catalyst Raney-Ni@C solid is placed in another quartz boat located in the downstream central heating zone of the dual-temperature zone tubular furnace, and the quartz boat is placed at the upper end of the downstream heating area, and the two porcelain boats are 13cm apart. After the sample is placed in the tubular furnace and before the heating process, the CVD system is evacuated three times with high-purity argon (99.99%), and ventilated for 15min to eliminate air and reduce the contamination of other gases to the experiment. Then, the downstream central heating zone is heated to a temperature of 250°C at atmospheric pressure, and the upstream central heating zone is heated to a temperature of 300°C. At this time, the gas system is set to argon 100s.ccm, and the insulation time is 2h. After the tubular furnace is cooled to room temperature, p-doped carbon-coated Raney nickel is obtained.
[0040] Example 2
[0041] A method for preparing a core-shell coated Raney nickel catalyst comprises the following steps:
[0042] (1) adding glucose to the Raney nickel aqueous solution, stirring to make it uniformly mixed, and then placing it in a reactor for hydrothermal reaction to obtain a wet product;
[0043] The specific process is to prepare the Raney nickel aqueous solution by alkaline leaching. Raney nickel uses nickel-aluminum alloy particles with a mass fraction of 48%-50% Ni and the rest Al. It is mixed with a sodium hydroxide solution with a mass fraction of 20%. The temperature of the process does not exceed 50°C. After the bubbles are generated and weakened, the process is slightly stirred. After the bubbles are generated and weakened, they are slightly stirred and activated for 4 hours under the condition of heating at 80°C, and then allowed to stand and precipitate. Fresh sodium hydroxide is replaced overnight, washed with distilled water until neutral, and stored in distilled water for use. 5g of glucose is added to the aqueous solution containing 10g of Raney nickel, stirred for 2h, and a uniformly mixed solution is obtained.
[0044] (2) vacuum drying the wet product and then calcining it in an inert atmosphere to obtain a core-shell Raney nickel catalyst;
[0045] The specific process is as follows: the uniformly mixed solution in step (1) is placed in vacuum drying for four hours, and then placed in a tube furnace and calcined at 800° C. for 5 hours in an argon atmosphere to obtain a core-shell Raney nickel catalyst Raney-Ni@C.
[0046] (1) The core-shell Raney nickel catalyst and the phosphorus source are sintered at high temperature under the protection of an inert gas to obtain a modified Raney nickel catalyst.
[0047] The specific process is as follows: During the synthesis process, in a dual-temperature zone tubular furnace, 1g NaH2PO2 is placed in a quartz boat located in the upstream central heating zone. 0.5g of core-shell Raney nickel catalyst Raney-Ni@C solid is placed in another quartz boat located in the downstream central heating zone of the dual-temperature zone tubular furnace and the quartz boat is placed at the upper end of the downstream heating area, and the two porcelain boats are 13cm apart. After the sample is placed in the tubular furnace and before the heating process, the CVD system is evacuated three times with high-purity argon (99.99%), and ventilated for 15min to eliminate air and reduce the contamination of other gases to the experiment. Then, the downstream central heating zone is heated to a temperature of 350°C at atmospheric pressure, and the upstream central heating zone is heated to a temperature of 300°C. At this time, the gas system is set to argon 100s.ccm, and the insulation time is 2h. After the tubular furnace is cooled to room temperature, p-doped carbon-coated Raney nickel is obtained.
[0048] Example 3
[0049] A method for preparing a core-shell coated Raney nickel catalyst comprises the following steps:
[0050] (1) adding glucose to the Raney nickel aqueous solution, stirring to make it uniformly mixed, and then placing it in a reactor for hydrothermal reaction to obtain a wet product;
[0051] The specific process is to prepare the Raney nickel aqueous solution by alkaline leaching. Raney nickel uses nickel-aluminum alloy particles with a mass fraction of 48%-50% Ni and the rest Al. It is mixed with a 20% sodium hydroxide solution. The temperature of the process does not exceed 50°C. After the bubbles are generated and weakened, the process is slightly stirred. After the bubbles are generated and weakened, it is slightly stirred and activated under the condition of heating at 80°C for 8h, then allowed to stand and precipitate, and fresh sodium hydroxide is replaced overnight. It is washed with distilled water until neutral and stored in distilled water for use. 5g of glucose is added to the aqueous solution containing 10g of Raney nickel and stirred for 2h to obtain a uniformly mixed solution.
[0052] (2) vacuum drying the wet product and then calcining it in an inert atmosphere to obtain a core-shell Raney nickel catalyst;
[0053] The specific process is as follows: the uniformly mixed solution in step (1) is allowed to stand, vacuum dried for four hours, and then placed in a tubular furnace and calcined at 800° C. for 5 hours in an argon atmosphere to obtain a core-shell Raney nickel catalyst Raney-Ni@C.
[0054] (3) The core-shell Raney nickel catalyst and a phosphorus source are sintered at high temperature under the protection of an inert gas to obtain a modified Raney nickel catalyst.
[0055] The specific process is as follows: During the synthesis process, in a dual-zone tubular furnace, 1g NaH2PO2 is placed in a quartz boat located in the upstream central heating zone. 0.5g of core-shell Raney nickel catalyst Raney-Ni@C solid is placed in another quartz boat located in the downstream central heating zone of the dual-zone tubular furnace and the quartz boat is placed at the upper end of the downstream heating area, and the two porcelain boats are 13cm apart. After the sample is placed in the tubular furnace and before the heating process, the CVD system is evacuated three times with high-purity argon (99.99%), and ventilated for 15min to eliminate air and reduce the contamination of other gases to the experiment. Then, the downstream central heating zone is heated to a temperature of 450°C under atmospheric pressure, and the upstream central heating zone is heated to a temperature of 300°C. At this time, the gas system is set to argon 100s.ccm, and the insulation time is 2h. After the tubular furnace is cooled to room temperature, p-doped carbon-coated Raney nickel is obtained.
[0056] Example 4
[0057] A method for preparing a core-shell coated Raney nickel catalyst comprises the following steps:
[0058] (1) adding glucose to the Raney nickel aqueous solution, stirring to make it uniformly mixed, and then placing it in a reactor for hydrothermal reaction to obtain a wet product;
[0059] The specific process is to prepare the Raney nickel aqueous solution by alkaline leaching. Raney nickel uses nickel-aluminum alloy particles with a mass fraction of 48%-50% Ni and the rest Al. It is mixed with a sodium hydroxide solution with a mass fraction of 20%. The temperature of the process does not exceed 50°C. After the bubbles are generated and weakened, the process is slightly stirred. After the bubbles are generated and weakened, it is slightly stirred and activated under the condition of heating at 80°C for 8h, then allowed to stand and precipitate, and fresh sodium hydroxide is replaced overnight. It is washed with distilled water until neutral and stored in distilled water for use. 5g of glucose is added to the aqueous solution containing 10g of Raney nickel and stirred for 2h to obtain a uniformly mixed solution.
[0060] (2) vacuum drying the wet product and then calcining it in an inert atmosphere to obtain a core-shell Raney nickel catalyst;
[0061] The specific process is as follows: the uniformly mixed solution in step (1) is allowed to stand, vacuum dried for four hours, and then placed in a tubular furnace and calcined at 800° C. for 5 hours in an argon atmosphere to obtain a core-shell Raney nickel catalyst Raney-Ni@C.
[0062] (3) The core-shell Raney nickel catalyst and a phosphorus source are sintered at high temperature under the protection of an inert gas to obtain a modified Raney nickel catalyst.
[0063] The specific process is as follows: During the synthesis process, in a dual-zone tubular furnace, 1g NaH2PO2 is placed in a quartz boat located in the upstream central heating zone. 0.5g of core-shell Raney nickel catalyst Raney-Ni@C solid is placed in another quartz boat located in the downstream central heating zone of the dual-zone tubular furnace and the quartz boat is placed at the upper end of the downstream heating area, and the two porcelain boats are 13cm apart. After the sample is placed in the tubular furnace and before the heating process, the CVD system is evacuated three times with high-purity argon (99.99%), and ventilated for 15min to eliminate air and reduce the contamination of other gases to the experiment. Then, the downstream central heating zone is heated to a temperature of 550°C at atmospheric pressure, and the upstream central heating zone is heated to a temperature of 300°C. At this time, the gas system is set to argon 100s.ccm, and the insulation time is 2h. After the tubular furnace is cooled to room temperature, p-doped carbon-coated Raney nickel is obtained.
[0064] Liquid phase hydrogenation device: The materials prepared in Examples 1-4 were respectively loaded with 0.2 g of catalyst in a fixed bed reactor and reduced with pure H2 or hydrogen and nitrogen at a maximum temperature of 80-120°C and a reduction time of 4-8 h. The temperature was lowered to 120°C, the hydrogen pressure was 0.8 MPa, the crude ethylene glycol product was used as the imported raw material, and the liquid hourly velocity LHSV = 2.2 h -1 The UV transmittance was measured at the feed and outlet, and the results are shown in Table 1.
[0065] Table 1 Transmittance data obtained by analyzing ethylene glycol after sample treatment in Examples 1-4
[0066]
[0067]
[0068] It can be seen from Table 1 that the degree of hydrogenation of ethylene glycol by selective hydrogenation using the catalyst provided by the present invention is high, especially at 275 nm, there is a significant increase in ultraviolet transmittance, the process is simple and has fewer by-products, and the process is simple and the main hydrogenated substances are carbonyl derivatives.
[0069] Therefore, the object of the present invention is to provide a method for improving the ultraviolet transmittance of ethylene glycol by Raney nickel catalytic hydrogenation. The method of the present invention is used to carry out efficient liquid phase hydrogenation reaction, the conditions are simple, the reaction can be carried out at a relatively low reaction temperature and reaction pressure, and the main hydrogenation substance is a carbonyl derivative. It provides a reference for the subsequent liquid phase hydrogenation of such reactants, so the technology has great economic value.
[0070] The above implementation examples have been described in detail the implementation process of the present invention, but the implementation methods of the present invention are not limited thereto. Ordinary technicians in the relevant technical field can achieve the purpose of the present invention based on the contents disclosed in the present invention. Any improvements and modifications based on the concept of the present invention fall within the protection scope of the present invention, and the specific protection scope shall be subject to the claims.
Claims
1. A method for preparing a core-shell coated Raney nickel catalyst, characterized in that: The following steps are involved: (1) adding glucose to the Raney nickel aqueous solution, stirring to make it uniformly mixed, and then placing it in a reactor for hydrothermal reaction to obtain a wet product; (2) vacuum drying the wet product and then calcining it in an inert atmosphere to obtain a core-shell Raney nickel catalyst; (3) The core-shell Raney nickel catalyst and a phosphorus source are sintered at high temperature under the protection of an inert gas to obtain a modified Raney nickel catalyst.
2. The method for preparing a core-shell coated Raney nickel catalyst according to claim 1, characterized in that: In step (1), the Raney nickel aqueous solution is prepared by an alkali leaching method; the specific process of preparing the Raney nickel aqueous solution by the alkali leaching method is as follows: nickel-aluminum alloy particles are mixed with a sodium hydroxide solution, slightly stirred for activation under heating conditions, and then allowed to stand for precipitation, and fresh sodium hydroxide is replaced overnight, washed with distilled water until neutral, and stored in distilled water for later use.
3. The method for preparing a core-shell coated Raney nickel catalyst according to claim 2, characterized in that: The heating temperature is 80-110°C and the activation time is 4-8h.
4. The method for preparing a core-shell coated Raney nickel catalyst according to claim 1, characterized in that: In step (1), the mass ratio of glucose to Raney nickel is 1:2-1:
4.
5. The method for preparing a core-shell coated Raney nickel catalyst according to claim 4, characterized in that: The temperature of the hydrothermal reaction in step (1) is 170-190° C., and the reaction time is 1-2 h.
6. The method for preparing a core-shell coated Raney nickel catalyst according to claim 1, characterized in that: In step (2), the calcination temperature is 780-820° C. and the calcination time is 5-6 hours.
7. The method for preparing a core-shell coated Raney nickel catalyst according to claim 1, characterized in that: In step (3), the high temperature sintering temperature is 250-550° C. and the insulation time is 2-3 hours.
8. The method for preparing a core-shell coated Raney nickel catalyst according to claim 7, characterized in that: The specific process of high-temperature sintering under the protection of inert gas in step (3) is as follows: in a dual-temperature zone tubular furnace, a quartz boat is loaded with a phosphorus source and placed in the upstream heating zone, and another quartz boat is loaded with a core-shell Raney nickel catalyst and placed at the upper end of the downstream heating zone; high-temperature sintering is performed under the protection of an argon atmosphere.
9. The method for preparing a core-shell coated Raney nickel catalyst according to claim 8, characterized in that: The phosphorus source is NaH2PO2; the heating temperature of the upstream of the double-temperature zone vacuum atmosphere tubular furnace is 300°C, and the heating temperature of the downstream is 250-550°C. The two temperature zones are heated simultaneously to reach the set temperature for insulation treatment.
10. A core-shell coated Raney nickel catalyst obtained by the preparation method according to any one of claims 1 to 9.